SISTEM MONITORING GETARAN KONTRUKSI JEMBATAN BERBASIS IOT - Wijayanto, Alif Arya; Suroyo, Heri Suroyo (ISTEK WIDURI, 2025)
Along with the development of Internet of Things (IoT) technology, monitoring the condition of bridge infrastructure can be done in real-time to improve the safety and durability of construction. This study aims to design and implement an IoT-based bridge vibration monitoring system using MPU6050 and SW-420 sensors connected to ESP32. This system is designed to detect vibration changes that can indicate potential damage to the bridge structure. The research method used is an experimental and quantitative method, by testing the tool on iron and concrete bridges. Data obtained from the sensor will be sent to a local MySQL-based server and displayed in graphical form via a PHP-based web interface. The test results show that the system can detect vibration variations according to changes in vehicle load, where heavier loads produce more significant fluctuations in the acceleration values of the X, Y, and Z axes. With this system, it is expected that bridge condition monitoring can be carried out more efficiently and accurately, so that managers can take preventive measures before more severe damage occurs. The results of this study can be a reference in the development of further bridge monitoring systems and the application of IoT technology in the infrastructure sector.